Interleukin-3 protects against viral pneumonia in sepsis by enhancing plasmacytoid dendritic cell recruitment into the lungs and T cell priming - Bénard, Alan; Hansen, Frederik J.; Uhle, Florian; Klösch, Bettina; Czubayko, Franziska; Mittelstädt, Anke; Jacobsen, Anne; David, Paul; Podolska, Malgorzata Justyna; Anthuber, Anna; Swierzy, Izabela; Schaack, Dominik; et al. (Frontiers in immunology, 2023)
Sepsis, a global health burden, is often complicated by viral infections leading to increased long-term morbidity and mortality. Interleukin-3 (IL-3) has been identified as an important mediator amplifying acute inflammation in sepsis; however, its function in the host response to viral infections during sepsis remains elusive. To investigate the role of IL-3 during viral pneumonia in sepsis.